Mixed micelles of the anionic surfactant sodium dodecyl sulfate and the nonionic pentaethylene glycol mono-n-dodecyl ether in solution - Feitosa, E.; Brown, W. (Amer Chemical Soc, 1998)
Dynamic light scattering, surface tension, and clouding temperature have been monitored to elucidate the solution properties of mixed micelles formed between the anionic surfactant sodium dodecyl sulfate (SDS) and the nonionic surfactant pentaethylene glycol mono-n-dodecyl ether (C12E5) over a wide range of surfactant concentration and temperature. Addition of 0.1 M NaCl shifts the relaxational modes to higher frequency and lowers the clouding temperature (T-c) of the nonionic surfactant solution by about 1 degrees C compared to the salt-free system. T-c for the mixed surfactant solutions is higher than that of the binary C12E5 solutions and depends sensitively on the concentration of the two surfactants but increases only slightly when the total surfactant concentration is increased at a given molar C12E5/SDS concentration ratio. With C12E5/SDS = 5.7, for example, T-c is 46.0 and 47.5 degrees C, respectively, at 5 and 70 mM of C12E5 the mixed solutions are homogeneous and stable and contain nonspherical micelles, which are close to monodisperse over a range of surfactant concentrations and temperature. The mixed system has a lower Krafft point than binary SDS solutions and shows an approximately ideal behavior in contrast to the binary C12E5 solution. The hydrodynamic radius (RH) of the mixed micelle increases with temperature as do C12E5 micelles in the binary solutions and also with increasing C12E5/SDS ratio. At 25 degrees C, the critical micelle concentration of the mixed solution lies between those of the individual surfactants and decreases as the C12E5/SDS ratio is increased.